Rancang Bangun Game Edukasi untuk Mata Pelajaran TIK Menggunakan RPG Maker MV di Kelas X SMK Negeri 6 Padang - Maulana S, Chaya; Irfan, Dedy (TSAQOFAH, 2026)
The rapid development of digital technology has driven innovation in education, particularly in the creation of interactive learning media that can enhance students’ motivation and engagement. One prominent approach is gamification, namely the application of game elements in the learning process to create more engaging and meaningful learning experiences. This study aims to design and develop game-based instructional media in the Role-Playing Game (RPG) genre that integrates Information and Communication Technology (ICT) subject matter at SMK Negeri 6 Padang. The development method employed is the Multimedia Development Life Cycle (MDLC), which comprises the stages of conceptualization, design, material collection, assembly, testing, and distribution. The resulting game presents an interactive storyline, educational missions, and quizzes based on course content as part of an enjoyable learning system. The findings indicate that this medium improves interactivity and learning effectiveness, as evidenced by expert evaluations and student responses categorized as “feasible for use,” with an average feasibility score of 94.04%. The implementation of gamification through this RPG is concluded to be an innovative solution in digital learning that has the potential to strengthen students’ understanding of ICT content in a more enjoyable, meaningful manner that is aligned with the demands of twenty-first-century learning.